PHILOSOPHICAL ANALYSIS OF THE CONCEPT OF LEGAL CONSCIOUSNESS, ITS ROLE AND IMPORTANCE IN THE DEVELOPMENT OF SOCIETY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explains the role of legal consciousness in the development of the country and the fact that the reforms carried out by the state are the main criterion for the development of the legal culture of young people. In addition, practical suggestions and recommendations for developing young people's legal awareness are provided.